Quality of life in patients having severe bronchial asthma - T. V. Smetanenko; O. S. Kobyakova (Бюллетень сибирской медицины, 2005)
Aimed at studying quality of life in bronchial asthma patients, 146 patients aged from 18 to 60 years having severe asthma were questioned using SF-36, AQLQ questionnaires. 63 patients had brittle asthma, 15 patients had fatal asthma and 18 patients had chronic asthma combined with persistent airway obstruction. Results: Brittle asthma influenced on «General Health» (31,8 ± 2,6)% and «Vitality» (30,0 ± 0,6)%; chronic asthma with persistent airway obstruction influences on «Physical Functioning» (25,83 ± 4,3)%, fatal asthma influenced on «Change Health» (45,0 ± 6,1)%, p < 0,05. Changes in mental sphere of quality of life are specific for patients having «brittle asthma», changes in physical sphere are specific for patients having chronic asthma combined with persistent airway obstruction.